(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Based on an incidental observation made in the context of the Swiss National Science Foundation (SNSF) Project 67 “End-of-life decision-making in extremely low birth weight infants in Switzerland”, this retrospective multicentre observational study aimed to analyse circumstances of delivery room deaths after late termination of pregnancy (LTOP) in Switzerland over a 3-year period. METHODS All delivery room deaths (including live and stillbirths) following LTOP among infants with a gestational age between 22 0/7 and 27 6/7 weeks at the nine Swiss level III perinatal centres between 1 July 2012 and 30 June 2015 were analysed. Indications for LTOP were classified as either (a) maternal emergencies or (b) fetal anomalies severe enough to cause significant maternal psychological distress. Whenever possible, specific diagnoses were recorded. Spontaneous intrapartum death and fetal death caused by injection of a cardioplegic drug were distinguished for stillborn infants. RESULTS A total of 465 delivery room deaths among extremely low gestational age newborns (ELGANs) were identified over the 3-year study period of the SNSF project. Of these, 195 (42%) occurred in the context of LTOP. Central nervous system malformations, chromosomal anomalies, severe congenital heart disease, multiple malformations and maternal emergencies accounted for 70% of all LTOPs. LTOPs resulted in live births in 76 (39%) cases. No correlation between gestational age and rate of live births was observed. Fetal death caused by injection of a cardioplegic drug was documented in only three cases. All infants born alive after LTOP died in the delivery room without resuscitation attempts. The use of drugs for palliative care in these patients was either rare or, alternatively, incompletely documented. CONCLUSION LTOPs contribute significantly to mortality rates among ELGANs and should therefore be included in perinatal registries. Uniform reporting of LTOPs should be established. Infants born alive after LTOP are entitled to comprehensive palliative care like any other infant born under different circumstances. Development of national guidelines for LTOPs (including the role of fetal death caused by injection of a cardioplegic drug and palliative birth as an alternative to induced abortion) would be highly desirable to guarantee acceptable standards of care.